2013
DOI: 10.1080/02723646.2013.832098
|View full text |Cite
|
Sign up to set email alerts
|

Effects of land use, slope gradient, and soil and water conservation structures on runoff and soil loss in semi-arid Northern Ethiopia

Abstract: Land degradation and recurrent drought are the major threats to rain-fed agriculture in the semiarid Ethiopian highlands. To reduce the risk of crop failure induced by moisture stress and to bring food self sufficiency through irrigation, water harvesting has become a priority in theGebeyehu Taye, Poesen, J., Van Wesemael, B., Vanmaercke, M., Daniel Teka, Deckers, J., Goosse, T., Maetens, W., Nyssen, J., Hallet, V., Nigussie Haregeweyn, 2013. Effects of land use, slope gradient, and soil and water conservation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
102
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 163 publications
(114 citation statements)
references
References 49 publications
10
102
2
Order By: Relevance
“…This finding was confirmed by runoff plots at several slope positions in the Maybar watershed (Bayabil et al, 2010) Taye et al (2013) in Tigray in the Ethiopian highlands in semi-arid monsoon climate agrees for experiments with large runoff plots. They found that the crop land had less runoff and erosion located on the relatively steeper hillsides than grass land on the land with less slope.…”
Section: Saturation Excesssupporting
confidence: 73%
“…This finding was confirmed by runoff plots at several slope positions in the Maybar watershed (Bayabil et al, 2010) Taye et al (2013) in Tigray in the Ethiopian highlands in semi-arid monsoon climate agrees for experiments with large runoff plots. They found that the crop land had less runoff and erosion located on the relatively steeper hillsides than grass land on the land with less slope.…”
Section: Saturation Excesssupporting
confidence: 73%
“…In addition, grazing in the basin has become more developed, with livestock quantities increasing from 468,800 in 1955 to 1,104,800 in 2011, a more than 2-fold increase. Unjustifiable human activities such as over grazing has caused a degradation and reduced ability of the earth's surface to retain rainfall-runoff, thereby accelerating the loss of water and soil [82].…”
Section: Human Activity Factormentioning
confidence: 99%
“…A study conducted by Nyssen et al (2009) in the northern highlands of Tigray shows that it is possible to reverse environmental degradation through an active, farmercentered SWC policy. Most of SWC focused studies conducted in northern Ethiopia looks at the effects to soil loss and run-off (Taye et al 2013;Gebremichael et al 2005;Selassie et al 2015) and food security (Van der Veen and Tagel 2011). From this perspective, we can quantify the vegetation cover improvement attributed to from the effects of SWC by using GIS and RS application in a basin which is not previously studied.…”
mentioning
confidence: 99%